Fundamental Operations of Language - Noam Chomsky (Cadernos de Linguística, 2020)
20 years ago, in lectures in Brasilia, I suggested that we might someday discover that the Faculty of Language (FL) is “beautifully designed, a near-perfect solution to the conditions imposed by the general architecture of the mind-brain in which it is inserted, another illustration of how natural laws work out in wondrous ways,” so that language is rather like a snowflake, and the near-perfect design can be expected to impose inefficiency of use. I added that “these are fables,” with the redeeming value that they “might even turn out to have some elements of validity. In the years since, solid reasons have been found to suggest that these hopes were understated, and that the “fable” – the Strong Minimalist Thesis – appears to have considerable validity. A number of striking and puzzling properties of FL – “universals of language” in the contemporary sense – have been shown to derive from the simplest computational operation, Merge, along with conditions of computational efficiency that are in effect part of natural law. And as anticipated, they do indeed impose communicative inefficiency.